2023
DOI: 10.1186/s40635-023-00501-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-to-moderate hyperoxia on lung injury in preclinical animal models: a systematic review and meta-analysis

Abstract: Background Extensive animal investigation informed clinical practice regarding the harmful effects of high fractional inspired oxygen concentrations (FiO2s > 0.60). Since questions persist whether lower but still supraphysiologic FiO2 ≤ 0.60 and > 0.21 (FiO2 ≤ 0.60/ > 0.21) are also harmful with inflammatory lung injury in patients, we performed a systematic review examining this question in animal models. Methods Studies retrieved from sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Hyperoxia also causes lung injury through the generation of reactive oxygen species 9,10,20 . Based on these observations, several randomized controlled trials have evaluated the e cacy of conservative oxygen therapy in critically ill patients [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia also causes lung injury through the generation of reactive oxygen species 9,10,20 . Based on these observations, several randomized controlled trials have evaluated the e cacy of conservative oxygen therapy in critically ill patients [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia can occur during sustained oxygen supply in critically ill patients, which can result in respiratory failure [899,900]. Hyperoxia is also an established model for oxidant-induced lung injury [901,902]. Previous reports of the group demonstrated that TLR4-deficient mice showed increased oxidant production in lung tissue and subsequent lung destruction [483], as well as enhanced susceptibility to hyperoxia-induced acute lung injury [903].…”
Section: Role Of Nox3 During Lung Diseasesmentioning
confidence: 99%
“…With great interest we have read the meta-analysis of Minkove et al . on the potential effects of low-to-moderate hyperoxia on lung injury in animal models [ 1 ]. They address potential harm from moderate hyperoxia (FiO 2 ≤ 0.6) exposure in the critical care setting, an important topic which has received limited attention as compared to exposure to severe hyperoxia (FiO 2 > 0.6).…”
mentioning
confidence: 99%